2008
DOI: 10.1590/s1413-86702008000600017
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access-related infections in HIV patients undergoing hemodialysis: case description and literature review

Abstract: Poor immune status, the use of a vascular access different from an AV fistula, and intravenous drug use (IDU) may favor increased rates of vascular access infections among HIV infected patients on hemodialysis. Staphylococcus spp. and Streptococcus spp. are the main cause of these infections, but Gram-negative rods and fungi have been found as well. Using an AV fistula when possible, and eliciting a history of IVDU on every visit may prevent this type of infection. When infections are present, coverage for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There are conflicting reports on the impact of HIV on vascular access infection rates in HIV. [16] Some studies have shown no differ ences between HIV-positive and HIV-negative patients, while others have shown that vascular access-related infections were more prevalent in those with lower CD4 counts, hepatitis B antigenaemia and injecting drug use. [17,18] The results of our study are different to these findings, as there were increased rates of admission for access-related infection in the HIV-positive group in spite of relatively well-preserved CD4 counts and low levels of hepatitis B antigenaemia.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports on the impact of HIV on vascular access infection rates in HIV. [16] Some studies have shown no differ ences between HIV-positive and HIV-negative patients, while others have shown that vascular access-related infections were more prevalent in those with lower CD4 counts, hepatitis B antigenaemia and injecting drug use. [17,18] The results of our study are different to these findings, as there were increased rates of admission for access-related infection in the HIV-positive group in spite of relatively well-preserved CD4 counts and low levels of hepatitis B antigenaemia.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Direct graft inoculation with bacteria or secondary seeding from bacteremia may explain the finding. 11 In contrast, a single-center review found no association between IV drug use history and arteriovenous infection in HIV-positive patients while adjusting for access type. 18 However, the outcome was restricted to infection requiring access removal, and other potential confounders were not controlled for, such as race.…”
Section: Discussionmentioning
confidence: 96%
“…Several of these studies are not risk adjusted. 11 In addition, few studies have evaluated whether risk factors differ between early infection, typically occurring at the incision site and arising from intraoperative contamination, and late infection, usually localized to the body of the graft because of inoculation during cannulation. 12 Querying the Vascular Quality Initiative (VQI) database, our primary goal was to describe the short-and longterm contemporary incidence and management of AVG infections.…”
mentioning
confidence: 99%
“…CKD and HD patients' immunity is suppressed, and HIV infection among these patients is not uncommon. In 2000, about 2% of HD patients had either HIV or AIDS, although the incidence was thought to be higher, [47] The prevalence of HIV in HD was heterogeneous; up to 40% of dialysis patients in urban centers had HIV. [48] HIV transmission between patients during HD sessions via HD machines has not been reported in the USA.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%